C.G. JUNG: um homem religioso? os sentidos da experiência religiosa em C.G. Jung - Oliveira, Marcos Fleury de (2012)
The main objective of this study is to deepen the religious thought of C. G. Jung as a possible expansion of knowledge in the field of Religious Science. Within the subdiscipline of Psychology of Religion, Jung can be considered as one of its main representatives and its most significant theoretical contributions covered a wide field of dialogue with philosophy, Christian theology, mythology and history of religions. However, his work needs further studies so that we can overcome a range of misunderstandings, besides interdisciplinary, theoretical and epistemological disputes. To achieve this end, we propose here to investigate the distinct layers of meaning of religious experience - the object of this work - in order to reflect the uniqueness and centrality of this notion in his theory and his worldview. Our hypothesis is that there is in Jungian thought a significant theoretical development from the time that Jung deepens the study of religions, which would allow us to recognize a new level in reference to what is traditionally called a religious experience, particularly within the Christian tradition. Jung seeks to move away from the atheistic reductionism of Freud, and also from the opposite position of the "omnipotence" and "omniscience" of theological discourse, trying to create a reserved niche of "knowledge" (gnosis / science) about the religious experience. In other words, Jung proposes and seeks to demonstrate that one could speak of the experience of God, validly and efficiently, without the corsets of metaphysics and theology. In support to our research we resorted on the canonical work of Jung, the work of commentators and letter-writing materials available